(untitled) (Research, Society and Development, 2022)
Aristotelian metaphysics, in its propositions for the study of being, aims at a wide spectrum of areas of knowledge that are not closed in themselves. It builds a hermeneutics of knowledge and helps to understand the Enlightenment movement, in addition to highlighting the Sciences more than empirical propositions, but also as a form and method for philosophical structuring. What we know is deeply marked by the way in which we get to know something, there being two main sources of knowledge in the subject: sensitivity, through which objects are given in intuition, and understanding, through which objects are thought in concepts. What defines objects is sensitivity, as the receptive/passive way in which we are affected by objects, and intuition is the direct way of referring to objects. The study of Being as Being, called First Philosophy, later, in the modern era, called pure reason, brings with it a proposal of science, and on this you will make the relationship with the Kantian proposal. This study consists of the analysis of separate forms of material aspects. In Aristotle, metaphysics can already be considered as a knowledge that maintains proximity to the idea of ​​mereology, that is, the relationship of the whole with the parts. We will see the Kantian categories above, thought in the light of the Aristotelian categories, will provide Kant’s critical philosophy with basic conditions to impose on reason the limits of possible experience. He intends, with this, to provide methodological rigor to metaphysics, freeing it from any dogmatic character and bringing it to the path of science, in which no questioning could occur. In this article, we aim, through Kantian prepositions, to establish Aristotelian metaphysics as the philosophical basis of the Enlightenment.